2016
DOI: 10.17338/trainology.5.1_1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of peak power output during exercises with similar lower-limb kinematics

Abstract: Objectives:The aim of this investigation was to compare peak power between the mid-thigh power clean, squat jump and push press. Design and Methods: Eleven recreationally trained men (age 22.2 ± 3.5 yrs; height 178.6 ± 8.5 cm; body mass 88.7 ± 13.5 kg) performed one set of three repetitions of the mid-thigh power clean, squat jump and push press, with 50, 60 and 70% of respective 1RM, while standing on two force platforms. The effect of load and lift on peak power was analyzed with two-way analysis of variance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 40 publications
2
18
0
Order By: Relevance
“…These differences may be due to Garhammer [ 24 , 26 ] evaluating world class weightlifters and due to the different devices, loads and methodologies used to assess power output, resulting in significantly different perceived power outputs [ 75 77 ]. Additionally, recent research reports high power outputs (3000–5600 W) in the push press exercise [ 78 80 ], similar to values reported for exercises with similar lower-limb kinematics, such as the jump squat or power clean [ 19 , 75 , 80 ].…”
Section: Previous Literature On Weightlifting Overhead Pressing Derivmentioning
confidence: 58%
See 4 more Smart Citations
“…These differences may be due to Garhammer [ 24 , 26 ] evaluating world class weightlifters and due to the different devices, loads and methodologies used to assess power output, resulting in significantly different perceived power outputs [ 75 77 ]. Additionally, recent research reports high power outputs (3000–5600 W) in the push press exercise [ 78 80 ], similar to values reported for exercises with similar lower-limb kinematics, such as the jump squat or power clean [ 19 , 75 , 80 ].…”
Section: Previous Literature On Weightlifting Overhead Pressing Derivmentioning
confidence: 58%
“…2 . According to the above-defined inclusion criteria, we identified 13 independent studies [ 16 , 24 , 26 , 50 , 72 – 74 , 78 80 , 85 – 87 ]. An overview of the main information from these studies can be found in the following sections, where the WOPDs and variations (see Table 2 ) and the main information regarding kinetics and kinematics results of the different studies analysed is provided (see Table 3 ) to guarantee a deeper knowledge of the WOPDs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations